2018
DOI: 10.3390/agronomy9010010
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Maturity Stage and Cold Storage Length Influence on Flavour Development in Peach Fruit

Abstract: Peach market is facing a constant decrease due to the poor fruit quality perceived at consumption that might be greatly affected by fruit ripening stage at harvest and by the post-harvest management. The present work aimed at clarifying the influence of maturity at harvest on the evolution of peach aroma and quality during shelf-life after prolonged cold storage. “August Flame” peaches were harvested at three maturity stages, determined based on IAD (index of absorption difference) and ethylene emission. Fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This shows that not all compounds from the ester family present high concentrations in mature stages. This is interesting since most studies report that these esters are found in high concentrations in mature fruits [ 11 ], but our results show that not all esters have the same behavior, and only some may be useful as indicators of complete maturity.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This shows that not all compounds from the ester family present high concentrations in mature stages. This is interesting since most studies report that these esters are found in high concentrations in mature fruits [ 11 ], but our results show that not all esters have the same behavior, and only some may be useful as indicators of complete maturity.…”
Section: Resultsmentioning
confidence: 68%
“…In addition to variety, the degree of maturation of the fruit has an effect on its VOC fingerprint [ 10 ]. VOC profiles have been shown to increment over the course of maturation in climacteric fruits, and a similar effect could occur in non-climacteric fruits also [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferreira et al [29] and Takeda et al [30] studied the harvest scheduling of fresh fruits and vegetables through machines to increase harvest efficiencies, such as the semi-mechanical system and the mobile platform machine. Ceccarelli et al [31] discussed the relationship between the harvest maturity stage and cold storage time. For distribution optimization, Lamsal et al [8] studied the agri-product optimal distribution scheduling from farm to warehouse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overall worldwide production is over 22 million tons. 11 It is cultivated in the mid hills of The Himalayas that extends from Jammu and Kashmir in the west to Khasi hills in the east. For about 1000-2000 m above sea level, Prunus persica 12 has a wide range of biologically active compounds that are rich in Phenolic acids, flavonoids, vitamins (significantly C and A), organic acids, antholyanim, antioxidants, dietary fibers and natural sugars.…”
Section: Introductionmentioning
confidence: 99%